2014
DOI: 10.1094/pdis-10-13-1059-re
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Effects of Sublethal Doses of Dimethachlon on Sclerotinia sclerotiorum

Abstract: A b s t r a c t -X. 2014. Stimulatory effects of sublethal doses of dimethachlon on Sclerotinia sclerotiorum. Plant Dis. 98:1364-1370.Growth and virulence stimulations of sublethal doses of fungicides on plant-pathogenic fungi and oomycetes have been reported and the stimulatory effects are potentially relevant to plant disease manage ment. Sclerotinia sclerotiorum is one of the most devastating and eco nomically important necrotrophic fungal phytopathogens, capable of infecting more than 400 species of plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 36 publications
0
13
1
Order By: Relevance
“…Hormesis is a generalizable biological concept, and the quantitative features of hormesis are consistent across a broad range of biological models and independent of chemical stressors, with the maximum stimulation magnitude being about 30-60% compared with the control (Calabrese 2015a). However, our previous study showed that the virulence stimulation magnitude of S. sclerotiorum by dimethachlone varied considerably and it seemed that larger stimulation magnitudes were obtained for dimethachlone-resistant isolates which usually have reduced virulence (Zhang et al 2019;Zhou et al 2014a). Therefore, the present study employed a group of S. sclerotiorum isolates with different levels of virulence to determine the correlation of the maximum stimulation magnitudes with virulence, and a significant negative correlation with P = 0.019 and R 2 = 0.439 was obtained.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Hormesis is a generalizable biological concept, and the quantitative features of hormesis are consistent across a broad range of biological models and independent of chemical stressors, with the maximum stimulation magnitude being about 30-60% compared with the control (Calabrese 2015a). However, our previous study showed that the virulence stimulation magnitude of S. sclerotiorum by dimethachlone varied considerably and it seemed that larger stimulation magnitudes were obtained for dimethachlone-resistant isolates which usually have reduced virulence (Zhang et al 2019;Zhou et al 2014a). Therefore, the present study employed a group of S. sclerotiorum isolates with different levels of virulence to determine the correlation of the maximum stimulation magnitudes with virulence, and a significant negative correlation with P = 0.019 and R 2 = 0.439 was obtained.…”
Section: Discussionmentioning
confidence: 73%
“…Given the unavoidable experimental random errors, smaller stimulation magnitude implies it is more difficult to obtain statistically significant stimulations. Previously, we have reported considerable stimulatory effects of dimethachlone on mycelial growth of dimethachlone-resistant isolates of S. sclerotiorum (Zhou et al 2014a). The greater mycelial growth stimulation magnitude of dimethachlone-resistant isolates may be related to the reduced mycelial growth rates compared with sensitive isolates (Zhou et al 2014b).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Also, the mycelial growths of fungi such as Lyophyllum palustre (Peck) Singer [ 241 ] and Phythium aphanidermatum , P. irregular and P. ultimatum were increased by propamocarb [ 242 ]. Besides, Phytophthora infestans growth increased as a result of the impact of metalaxyl [ 243 ] and Sclerotinia sclerotiorum under treatment with dimethachlon conditions [ 244 ].…”
Section: Effects Of Heavy Metals On Fungimentioning
confidence: 99%
“…Several chemical agents registered in the USA, Canada, Australia, Europe and China are available to this purpose. Their active ingredients are: boscalid, fluazinam, fluxapyroxad, pyraclostrobin, penthiopyrad, picoxystrobin, prothioconazole, prothioconazole and trifloxystrobin, tetraconazole, thiophanate methyl (Matheron and Porchas 2004;Bradley et al 2006;Zhou et al 2014aZhou et al , 2014bWang et al 2015;Derbyshire and Denton-Giles 2016). The effective control of S. sclerotiorum requires application of fungicides during sensitive time frames, the number of treatments depending on the length of the crop vegetation period and on how long flowers or petals are available for infection by ascospores (Heffer Link and Johnson 2007).…”
Section: Introductionmentioning
confidence: 99%